Dance Library: performance telling and reenactment as acts of fiction (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article was dedicated to exploring an articulation between performance telling and reenactment (Machado, 2014), in connection with the choreographic installation Dance Library (Neto Machado, Jorge Alencar, Dimenti), as practices composed of affects, narratives, scenes, and bodily inscriptions elaborated through the intensity of encounters with diverse art works and their resonances. To this end, notions such as artist historiography (Small, 2019), oralitura (Martins, 2020; 2021), and fiction (Le Guin, 2021) are interwoven with a series of other national and international artistic creations.
Keywords: performance telling; Reenactment.; fiction; dance Library